Pela Dan Gandong Culture As Basic of A Network Formation For Poverty Alleviation In The Village - Titaley, Elsina (Advances in Social Sciences Research Journal, 2018)
Poverty is remaining a major topic in the world community in the recent years. Therefore, it is needed a good concept in reducing poverty. The new concept offered in the context of indigenous peoples is pela and gandong culture which is a strong attribute in Moluccas poverty alleviation. Pela and gandong have existed since ancestral times and have remained guarded to this day. This concept is built on the basis that pela and gandong is a local community culture that helps each other to help one community with another. Life by helping each other is obligatory, not based on coercion but naturally. If this concept is effectively implemented it will contribute to poverty alleviation. The purpose of this study is to analyze the pela and gandong culture as a basis of network to eradicate rural poverty in Lomoli Village. This research is something new that is rarely studied in the context of indigenous peoples. The research sites selected is Lumoli village, which is still thick with pela and gandong concept. The implications of this research are to provide new resolutions to communities and governments in the pela and gandong context as a good foundation for building strong indigenous people in alleviating rural poverty